PENGUATAN NILAI KARAKTER MELALUI PROJEK P5 PADA DIMENSI KREATIF DISEKOLAH DASAR - Lisa Anggreyni; Siprianus Jewarut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the Implementation of the Pancasila Student Profile Strengthening Project (P5) in shaping student character in the Creative dimension in grade V of SD Negeri 01 Bengkayang. The problems raised focus on P5 activities in fostering character values ​​such as responsibility, politeness and creativity. The method used in the study was a qualitative descriptive method with data collection techniques through observation, interviews, questionnaires and documentation. The results of the study showed that the implementation of P5 in schools can improve student character in the creative dimension, as seen from student participation in projects, the ability to find new ideas in making projects. In addition, character values ​​in responsibility, politeness, cooperation and creativity also developed through the implementation of P5 in learning. In conclusion, P5 can be an effective strategy in instilling character values ​​from an early age, especially in the creative dimension through fun and meaningful activities.